An arsenic resistant bacteria isolated in Tucumán, Argentina, as a model microorganism for astrobiology studies. - Maizel, Daniela (2015)
Astrobiology can be defined as a multidisciplinary science that focuses on studies about the origin, evolution, distribution and future of life in the Universe (https://astrobiology. nasa.gov/nai/).In the last 20 years, studies of extrasolar planets have progressed considerably, focusing on the search of planets similar to Earth and in the Habitability Zone (HZ), with a major interest in the search of evidence of life in such environments. It is readily evident that our notion of ?habitability? relies on our limited knowledge of life on Earth. Therefore, in an attempt to find possible forms of life in extraterrestrial systems, it becomes fundamental to enlarge our knowledge about extreme life forms inside our own planet. Such forms of life able to tolerate extreme conditions are mostly known as ?extremophiles? (Caviccioli 2002; Das Sarma, 2006). Some of these organisms have been recently proposed as models for astrobiology studies (Abrevaya et al, 2010; 2011).An interesting case of extremophiles is represented by arsenic- resistant bacteria. Arsenic is a toxic metalloid widely spread in nature. It generally occurs as either arsenate [HAsO42- or As(V)] or arsenite [H2AsO3 or As(III)], the latter species being more toxic than the former. It can be released either by natural weathering of rocks or by anthropogenic sources (Muller et al., 2003). Arsenic is toxic because As and P are similar enough that living organisms attempt this substitution (Wolfe-Simon et al, 2009). Although arsenic is toxic to almost every form of life, it has been previously demonstrated that microorganisms can resist it and also utilize arsenic compounds as a source for growth (Krumova et al., 2008). It has been previously suggested that arsenic-based forms of life could be present on Earth within a ?shadow biosphere?, in similar environments to the ones found outside of the Earth (Davies et al, 2009). These alternative forms of life could currently exist in arsenic-rich environments as much as inside Earth itself as in extraterrestrial systems (Cleland & Copley, 2005; Davies et al, 2009). Even though all known life requires phosphorus (P) in the form of inorganic phosphate, In 2010 Wolfe-Simon et al. reported on a bacterial strain isolated from Mono Lake (California, USA) known as GFAJ-1, which is able to survive in high arsenic concentrations and in the absence of phosphorus. The authors of the work suggested GFAJ-1 as a habitability model in other planets, where different forms of life could be based on arsenic (Wolfe-Simon et al, 2011).Brevibacterium linens AE038-8, is a bacterial strain isolated from As-contaminated groundwater in Tucumán (Argentina), highly resistant to arsenic compounds and capable of growing in extremely low phosphate concentrations, showing a physiology comparable to that of GFAJ-1. It?s recently sequenced genome (Maizel et al, 2015) revealed the presence of arsenate reductase enzymes previously described, which might have evolved from arsenic-rich environments in early life on Earth (Wolfe-Simon et al, 2009). Therefore, we propose strain AE038-8 as an interesting prospect for studies of life in extrasolar planets.